Mumble - Brent, Peter ([N.S.W.]: Mumble Communications, 1996)
Web site on Australian politics, ideologies, elections, and parties. Includes examples of Brent's print journalism.
Title from title screen (viewed on 8 July 2004)
Text and graphics.
Mode of access: Internet via World Wide Web. Available at: http://www.mumble.com.au
Selected for archiving
Keywords: Election forecasting -- Australia; Elections -- Australia; Political parties -- Australia -- Platforms; Political parties -- Australia; Political science -- Australia